31 Quality or Quantity? An Analysis of the Colorectal Cancer Resection Volume-Outcome Relationship From the 2019 National Bowel Cancer Audit Data. (28th February 2022) - Gujjuri, R.; Kawka, M.; Murphy, J.
Abstract: Aim: Despite increasing evidence supporting cancer services centralisation, no consensus exists in the association between high-hospital or high-surgeon volume and mortality following colorectal cancer surgery. This study aimed to identify and characterise a volume-outcome relationship in colorectal cancer. Method: National Bowel Cancer Audit (NBOCA) dataset was combined with the Association of Coloproctology of Great Britain and Ireland (ACPGBI) Clinical Outcomes Publication (COP) 2019 report. Adjusted 90-day and 2-year mortality were derived from patients included in the 2018 and 2016 datasets, respectively. The impact of centre volume, surgeon volume and ACPGBI membership rates on outcomes was assessed. Cumulative sum (CUSUM) analysis was performed to identify the centre and surgeon volume threshold. Results: 144 hospitals were included, with 17, 235 and 17, 703 patients from the 2018 and 2016 datasets, respectively. 781 surgeons were identified, with 478 holding ACPGBI memberships. No significant difference was found between centre or surgeon volumes for adjusted 90-day and 2-year mortality. High ACPGBI membership rates were significantly associated with a reduced 90-day (p=0.006), but not 2-year mortality (p=0.198). CUSUM analysis found 36 per year as threshold centre volume (p=0.003) and 15 surgeries per year as the threshold surgeon volume (p=0.241). Conclusions: The high degree of existing centralisation for cancer services in the UK limits the number of true low-volume centres compared to other countries. Surgeon volume may be a better predictor of colorectal cancer surgery outcomes than centre volume. More granular data is needed to improve the current understanding of the association between surgeon volume, ACPGBI membership and outcomes in colorectal surgery.